Exercise immunology: future directions for research related to athletes, nutrition, and the elderly - Nieman, D. C. (International Journal of Sports Medicine, 2000)
This article examines three questions related to exercise immunology: 1) Can exercise attenuate changes in the immune system related to aging? The few research papers available suggest that the answer may be "yes", but exercise training may have to be long-term and of sufficient volume to induce changes in body weight and fitness before any change in immunity can be expected in old age. 2) Is the athlete an immunocompromised host? For most athletes, probably not, although the answer may be 'yes' during certain periods when the athlete exceeds normal training limits or competes in endurance events. Most studies have reported that the immune systems of athletes and nonathletes in the resting state are more similar than disparate with the exception of natural killer cell activity which tends to be elevated in athletes. Infection risk may be more related to the acute changes in immunity that occur following heavy exercise, but this hypothesis has not been sufficiently studied. 3) Are nutrition supplements effective countermeasures to exercise-induced inflammation and immunosuppression? Except for carbohydrate, the answer at this time for all other nutrients studied is 'no'. While data from the vitamin and mineral studies have been negative, and those involving glutamine conflicting, several investigations indicate that carbohydrate compared to placebo ingestion is associated with attenuated hormonal and immune responses.